Value management as a cost control approach to improve project with value for money during design stage - Yeo, Han Ming; Lee, Benny Hai Chim (INTI International University, 2018)
Value Management (VM) is a methodology that has been adopted to facilitate decision-making on construction projects to deliver ‘value for money’ for clients[1]. It provides various approach to meet project needs and functions as required by the clients. This paper aims to investigate the needs of VM practice in the Malaysian construction industry. This paper employs quantitative approach by distributing total 313 numbers of questionnaire to various construction firms. It is indicated that VM is a worthwhile practice to enhance value and achieve cost savings for construction project. However, design liability related issue and adversative attitude of original design team are the main problems of VM practice. It is also found that VM practice has great potential to impact life cycle costing and performance of construction projects.